Wet carbonation of C3A and pre-hydrated C3A - Villmow, Sophia; Mielkau, Anika; Götz-Neunhoeffer, Friedlinde; Neubauer, Jürgen (Cement and Concrete Research, 2023)
The carbonation of C3A and pre-hydrated C3A was studied at different initial pH values, temperatures, pre-hydration and carbonation times. Based on these investigations, the reaction kinetics of C3A under humid conditions were considered in more detail. The reaction products were characterized by quantitative X-ray diffraction (QXRD) and thermogravimetric analysis (TGA). C3A shows no significant reaction when carbonated directly in suspension, however, it has been observed that pre-hydrated C3A can be carbonated. A higher reaction degree was obtained with increasing hydration time. Consistent with reaching a stable pH, no further reaction of the hydrate phases was detected after 20 min, indicating fast kinetics of the carbonation reaction. At temperatures ≤21 °C, the CaCO3 polymorph vaterite was found to be the main phase. At a pre-hydration temperature of 40 °C, C3AH6 appeared as a stable hydrate phase, but showed no reaction with CO2 under our experimental conditions.
CRIS-Team Scopus Importer:2023-07-28
Keywords: C; Carbonation (C); Carbonation products (B); CO; pH (A); Reaction kinetics (A); Thermal analysis (B); X-ray diffraction (B)